António Lobo Antunes, leitor: leitor - Glaura Aparecida Siqueira Cardoso Vale (2013)
This thesis aims to investigate the reading and writing scene in António Lobo Antunes based on an analysis of his war letters, articles and of the episodes of the three novels that make up his autobiographical memory, Memória de elefante (1979), Os cus de Judas (1979), Conhecimento do inferno (1980). These texts show that reading and writing are ruled by areversibility and that they are not, therefore, distinct and independent processes in the author´s work. The complex war situation as scene and condition of production is implicated in his first novels and chronicles which, associated with the letters that brand that cycle, are an important research material in order to verify this reversibility. It is worth noted the urgency of a project (the books to come), the awakening of his endless work of observation and sieving of the reader Lobo Antunesmemory corroborating the composing of his writing. In this regard, the cultural references along his work that point out a reading scene ratified by hiswriting (integrating that readers memory either as research topic for his literary project, or as an element for the elaboration of his work) will be investigated as well as it will be considered the construction of a virtual circular library. Based on this proposition and according to Walter Benjamin, it is argued that the term cultural reference can be taken as trace, vestige, trail of the presence of something that has already become absent.